Description Of Antihypertensive Drugs Use In Hypertensive Outpatients With Diabetes Mellitus At Panembahan Senopati Bantul Hospital - A Hi Wahid, Rahmat; Febri Nilansari, Anis; Andriani Fatimah, Fitri (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2024)
Hypertension (HT) is still a health problem in the world, including in Indonesia. Hypertension in patients with type 2 diabetes mellitus (T2DM) will have an impact on worsening conditions and multi-complications, including macrovascular, microvascular, and insulin resistance complications. This can be prevented by providing appropriate and rational therapy so that the effectiveness of therapy is achieved and avoid worsening conditions and complications. This study aims to determine the pattern of antihypertensive drug use in HT patients with comorbid T2DM in the outpatient installation of Panembahan Senopati Hospital, Bantul for the period of August 2023. The study was designed with a descriptive non-experimental method, cross-sectional with a retrospective approach. The source of research data is secondary data derived from medical records of HT patients with T2DM for the period of August 2023 with data collection by purposive sampling. A total of 157 HT patients met the inclusion criteria in this study with the prevalence of women (n = 106; 67.50%) and men (n = 51; 32.50%), most ages in the 55-65 year range (n = 57; 36.30%). A total of 66 patients (42.10%) received monotherapy, while 91 (57.90) patients received polytherapy. Candesartan (n=80; 27.68%) and Amlodipine (n=78; 26.99%) monotherapy with oral administration were the most common treatment options in this study. Overall, the most widely used drug classes were Angiotensin Receptor Blockers (ARB) (41.18%), Calcium Channel Blockers (CCB) (32.5%), and Diuretics (14.1%). While the most common combination of drug groups is ARB + CCB (24.8%). This study concluded that the use of drugs mainly was polytherapy and in general the use of antihypertensive drugs consisted of 7 classes of drugs namely Angiotensin Receptor Blockers, Calcium Channel Blockers, Diuretics, ẞ- blockers, Centrally-acting Agents, ACE-Inhibitors, Vasodilators